Conceptual framework & accounting standards - Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2021)
This book is intended for students taking up the CHED-required subject "Conceptual Framework and Accounting Standards." The Philippine Financial Reporting Standards (PFRS) are highly technical. My aim in writing this book is to present concepts in a manner that would make sense to all learners - CPA aspirants and non-CPA aspirants alike.
Overview of accounting -- Conceptual framework for financial reporting -- PAS 1 Presentation of financial statements -- PAS 2 Inventories -- PAS 7 Statement of cash flows --> PAS 8 Accounting policies, changes in accounting estimates and errors -- PAS 10 Events after the reporting period -- PAS 12 Income taxes -- PAS 16 Property, plant and equipment -- PAS 19 Employee benefits-- PAS 20 Accounting for government grants and disclosure of government assistance -- PAS 21 The effects of changes in foreign exchange rates -- PAS 23 Borrowing costs -- PAS 24 Related party disclosures -- PAS 26 Accounting and reporting by retirement benefit plans -- PAS 27 Separate financial statements -- PAS 28 Investments in associates and joint ventures -- PAS 29 Financial reporting in hyperinflationary economies -- PAS 32 Financial instruments: presentation -- PAS 33 Interim financial reporting --PAS 36 Impairment of assets -- PAS 37 Provisions, contingent liabilities and contingent assets -- PAS 38 Intangible assets -- PAS 40 Investment property -- PAS 41 Agriculture -- PFRS 1 First-time adoption of Philippine financial reporting standards -- PFRS 2 Share-based payment -- PFRS 3 Business combinations -- PFRS 5 Non-current assets held for sale and discontinued operations -- PFRS 6 Exploration for and evaluation of mineral resources -- PFRS 7 Financial instruments: disclosures -- PFRS 8 Operating segments -- PFRS 9 Financial instruments -- PFRS 10 Consolidated financial statements -- PFRS 11 Joint arrangements -- PFRS 12 Disclosure of interests in other entities -- PFRS 13 Fair value measurement -- PFRS 14 Regulatory deferral accounts -- PFRS 15 Revenue from contracts with customers -- PFRS 16 Leases -- PFRS 17 Insurance contracts -- Reference
Includes bibliographical references.
Keywords: ACCOUNTING